INDONESIAN GOVERNMENT POLICY IN FOREST FIRE HANDLING - Nazifah, Nazifah; Yarni, Meri; Amin Nasution, Muhammad (Jurusan Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2020)
Since 1997 until now, forest and land fires (Karhutla) in Indonesia occur almost every year. The 2015 Karhutla incident is believed to have burned 2.61 million hectares of forest and land. In 2016, even though Indonesia was hit by La Nina, forest and land fires continued to burn forest and land area of 14,604.84 hectares. Forest and land fires have a detrimental impact on the environment, social and economy. Even the problem of fires in Indonesia has caused smoke problems for neighboring countries, especially in the Southeast Asia region. The government has tried to deal with the forest and land fires both in the form of regulations and programs, but the forest fires still occur. Several studies have shown problems in handling forest and land fires, including difficulties. The government itself is aware that forest and land fire is a multidimensional problem that requires cross-sectoral coordination to deal with it.Â Keywords: forest fires, Indonesia, policy